Bluegrass Ambassadors : The McLain Family Band in Appalachia and the World - Jenkins, Paul O. (Book collections on Project MUSE., 2020)
"Bluegrass Ambassadors is the first book-length study of the McLain Family Band, which has spread the gospel of bluegrass for more than fifty years. An act rooted in bluegrass that also collaborated with classical composers and performed folk, jazz, gospel, and even marches, the McLain Family Band traveled to sixty-two foreign countries in the 1970s, touring under the auspices of the State Department. After retiring as full-time performers, most members of the group became educators, with patriarch Raymond K. McLain's work at Berea College playing a particularly important role in bringing bluegrass to the higher education curriculum"--